Suara Kenabian Amos: Teladan Bagi Pengkhotbah di Era Industri 5.0 - Esron Mangatas Siregar; Indah Hotlan Imanda Saragih (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2023)
This research is motivated by the occurrence of violations and deviations from the prophetic voice of Amos, which have massively occurred in the fields of law, society, and spirituality. The law is twisted, blunt on top, and sharp on the bottom because the judicial system, as a place to seek justice, is not functioning properly and corruption is rampant, disregarding the poor and treating humans as worthless shoes. The priests choose wealth, positions, and compromise with sin. This happens due to an unclear calling that the LORD is summoning, where the Bible no longer serves as a benchmark for sermons, replaced by pleasing speeches for the listeners and compromising with sin. Through qualitative research methods and literature review in the book of Amos, as well as interviews, the results of the analysis indicate that the prophetic voice in the book of Amos produces a firm, uncompromising attitude, and courageously confronts challenges in proclaiming the prophetic voice, all of which serve as guidance for preachers in the era of Industry 5.0.